BioEssays 12/2019. (27th November 2019) - Ritschard, Elena A.; Whitelaw, Brooke; Albertin, Caroline B.; Cooke, Ira R.; Strugnell, Jan M.; Simakov, Oleg
Abstract : Cephalopods provide a unique model system to investigate how organismal novelties evolve. In article number 1900073, Elena A. Ritschard et al. discuss how co‐evolutionary signatures among various genomic characters have contributed to cephalopod organismal novelties and can be used to dissect their functional organization. Cover illustration by Hannah Schmidbaur.